A study on multi-level franchising in Singapore. - Ng, Regina Yan Yi. (2008)
This paper looks at a new business expansion model comprising of elements of MLM and franchising. The objective of introducing this model is to enable SME owners to expand their business further and reap greater returns. Ngee Ann Optical is used as a case study to show how our proposed business model will work in doubling its operating profits within four years.